Faktor-Faktor Yang Berhubungan dengan Kejadian Baby Blues Syndrome Pada Ibu Postpartum di Wilayah Kerja Puskesmas Teling Manado - Dwi Winarsih; Silvia D. Mayasari Riu; Irma M. Yahya (Medical Laboratory Journal, 2025)
Baby blues syndrome is a common condition experienced by mothers after childbirth and can negatively impact both the mother and her baby. Several contributing factors include lack of mental preparedness due to young maternal age and limited parenting experience, as well as the number of children a mother has. This study aimed to identify the factors associated with the occurrence of baby blues syndrome at the Teling Community Health Center in Manado. This was an observational analytic study using a cross-sectional design. The sampling technique applied was simple random sampling with a total of 59 respondents. Data collection was conducted using the Edinburgh Postpartum Depression Scale (EPDS) questionnaire. Data were analyzed using the SPSS program and the Chi-Square test at a significance level of α = 0.05. The results revealed a significant relationship between maternal age and the occurrence of baby blues syndrome (P-value = 0.000 < α 0.05), as well as between parity and baby blues syndrome (P-value = 0.008 < α 0.05). In conclusion, maternal age and parity are significantly correlated with the occurrence of baby blues syndrome at the Teling Health Center. It is recommended that nurses, as healthcare providers, address not only the physical needs of postpartum mothers but also their psychological well-being. Early identification of emotional disturbances and collaboration with other healthcare professionals in providing counseling and promoting bonding between mother and baby during the postpartum period are essential to ensure optimal maternal mental health and healthy infant development